(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article discusses the development of a wireless monitoring system for the control of toxic and combustible gases to solve the actual problem of automated control of the gaseous environment at hazardous production facilities. The architecture of the monitoring system, which consists of wireless gas analyzers with connected remote digital modules, is described . The article discusses design and circuit solutions for the development of a digital gas sensor module, which includes: a microcontroller, an RS-485 transceiver, an integrated power supply based on a pulse converter, a unit with digital gas sensors. The principle of combined protection against electrostatics and microsecond interference, as well as the concept of digital gas sensors with sensitive elements of various physical types, is considered. The developed module makes it possible to detect explosive and toxic gases in the atmosphere, and can be used in industrial accident prevention systems together with actuators.